Empirical Analysis of Monetary Policy and Economic Growth in Nigeria (1990-2022) - Musa, Ibrahim; Ahmad, Abdullahi Idris (Integrated Journal of Business and Economics (IJBE), 2024)
This study examines the effects of monetary policy on economic growth in Nigeria throughout 1990-2022. The Autoregressive Distributed Lag (ARDL) bound cointegration is employed to analyse both the short-term and long-term dynamics. The research incorporates various monetary policy instruments as variables, namely Broad Money Supply (MS), Interest Rate (INTR), Inflation Rate (INFR), and Exchange Rate (EXR). Additionally, Economic Growth is measured by the Real Gross Domestic Product Growth Rate (RGDP). It utilises published data from the Central Bank of Nigeria (CBN). Results indicate the long-term statistical significance of the money supply (MS), inflation rate (INF), and exchange rate concerning their impact on the Growth Rate of RGDP. In the short run, it was seen that the MS exhibited statistical significance and exerted a positive influence on RGDP. Conversely, both INTR and EXR were statistically significant and were associated with a negative and significant association with RGDP. Consequently, the study suggests implementing monetary policy to cultivate a conducive investment climate. This may be achieved by promoting market-driven interest and currency rates, stimulating domestic investment, and enticing foreign direct investment.